The Employment Competency Model for Good Management of Dali University Graduates - Li, Xiru; Noichun, Nuntiya (วารสารการวิจัยการบริหารการพัฒนา, 2025)
This study develops an employment competency model for good management of Dali University graduates. In the face of an increasingly competitive job market, graduates encounter significant challenges in aligning their competencies with industry demands. Employing a mixed-methods approach, this research evaluates both the current status and the needs of Dali University graduates concerning employment competency. The study identifies critical gaps in general skills, career planning, and environmental competitiveness and proposes targeted guidelines for addressing these deficiencies. These recommendations underscore the importance of integrating practical training, enhancing career development resources, and leveraging external support to boost employment competency. The study’s findings contribute to refining the employment competency model, ensuring that educational outcomes meet market expectations and facilitating successful career transitions and sustained professional growth for Dali University graduates.